Cabaran Penggunaan Sistem Sensor di Bangunan Pejabat Komersial Hijau - Mohamad, Nur Nabihah; Omar, Roshartini (Research in Management of Technology and Business, 2021)
Sensor systems are important to increase awareness of environmental monitoring as well as provide safety and surveillance benefits. It is clear that the sensor system is a basic automation element with the ability to fill the building environment. A signal sensor that is not routed to a microprocessor will process the data and is capable of providing information output to external users. Therefore, the objective of this study is to identify the types of sensors used in green commercial office buildings, study the problems of the use of sensor systems in green office buildings and strategies to improve the use of sensor systems in commercial office buildings. This study was conducted in the state of Johor by using quantitative methods that interpret the questionnaire instrument and all data obtained from the questionnaire analyzed using SPSS 17.0 software. A total of 50 respondents using and 50% response rate were involved in this study consisting of deployment managers, project managers and engineers The results showed that the highest types of sensors used in green commercial office buildings were analog and digital types. The most critical problem of the use of sensor systems is the security challenge. To that end, the majority of respondents strategizing strategies to increase the use of sensor systems are best with strategic strategies such as providing remuneration and tax incentives from the government to organizations that want to adopt system sensors on their companies. Therefore, the study is to benefit the academic field as a guide and reference to students doing new research, as well as to the construction industry for the use of this sensor system in managing their buildings in the future.